Implementasi Nilai-nilai PAI dalam Surah Luqman Ayat 19: sebagai Alternatif Pembentukan Karakter Peserta Didik pada Era Modern. - Ahmad Fadhlulloh; Muhammad Yunan Yusuf (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Character education plays a crucial role in shaping students' personalities to be faithful, pious, and virtuous. However, the development of globalization and digital technology has given rise to various moral issues, such as poor communication ethics, increasing individualism, and the degradation of social attitudes. In this context, Islamic Religious Education (PAI) plays a strategic role as a means of character development based on the values ​​of the Quran. One relevant verse is Surah Luqman, verse 19, which emphasizes humility and gentleness in communication. This study aims to analyze the character education values ​​in Surah Luqman, verse 19, and its relevance as an alternative for character development in students in the modern era. The method used is library research with a descriptive-analytical approach to various scientific literature and Quranic interpretations. The results of the study indicate that the values ​​of simplicity and communication ethics in this verse are relevant to the needs of 21st-century character education. Its implementation can be achieved through Islamic Religious Education (PAI) learning, teacher role models, positive habits, and the educational use of digital technology to strengthen students' Islamic character.